Counsellors’ Competence in Managing School Related Crises in Southwestern Nigerian Universities, Nigeria - Esther, Lawal Oluwabukola; Olusegun, Atoyebi Adeola (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
The study ascertained the availability and adequacy of trained guidance counsellors in south-western Nigerian universities. It also investigated the common crises in the universities; determined and examined the level of counsellors’ competence in managing crises in South-western universities. These were with a view to providing information on some factors that could influence crises management in the universities by universities guidance counsellors. The study adopted a descriptive survey research design. The population for the study comprised all guidance counsellors in southwestern Nigerian Universities. The sample size comprised 128 respondents in southwestern universities and three states (Osun, Oyo and Ogun) were also selected from six states (Oyo, Osun, Ogun, Ekiti, Ondo and Lagos) in southwest Nigeria using simple random sampling technique. Two instruments were used to elicited information for the study, namely: Checklist of Availability & Adequacy of Counsellors (CAAC) and Counsellors’ Competence Scale (CCS) Data collected were analyzed using percentage, chis-square and multiple regressions. The result showed that the availability and adequacy of trained guidance counsellors in Southwestern Nigeria universities were not adequate, federal 27(93.1%) state 19(100.0%) and private 35(97.2%). The result also revealed common crises in the southwestern Nigerian universities showing truancy has the commonest crisis in the school with 3(4.0%), followed by drug abuse 9(10.9%) , cultism is the third one 9(10.9%)and so on. Furthermore, the result of this study showed how competent school counselors are, with federal universities having the most competent counselors 8(27.6%), followed by state university with 4(21.0%) and private university with 7(19.4%). The result showed the difference in the competence of the universities counsellor based on the institutions F-ratio (F = 3.409 and Sig = 0.035), the difference in the competence of the universities counsellor based on the institutions is significant at p < 0.05.It was concluded that counselor competence had significant relationship with school crises management.